Sisi Terang dan Gelap: Digitalisasi pada Perkembangan Pendidikan Indonesia - Delia Maharani; Latifah Meynawati (Universitas Maritim AMNI Semarang, 2024)
As time goes by, humans continue to adapt to the environment of their era, developing innovations to make their lives more efficient and practical. In this effort to adapt and change, technology has become a tool that is greatly utilized by humans. In the current era of even development of information technology, education has a very important role because it is needed to provide meaning to every subject matter, which will help Indonesia move towards a more advanced civilization. For this reason, this article aims to examine two different sides to the digitalization of school education in facing the era of revolution 4.0 towards 5.0 in Indonesia today. This research uses descriptive qualitative research with a literature review method. The research results show that there are various applications of digitalization/technology in education that have both good and bad impacts. This impact occurs in aspects of learning and administrative services which will of course influence the development of education, therefore it is necessary to design appropriate strategies as preventive and overcoming measures, especially these negative impacts. So that education in Indonesia is expected to be able to rise amidst world civilization and demonstrate its existence by presenting creative solutions to various global challenges that arise in the current and future eras.